Radiofrequency Ablation of Benign Symptomatic Thyroid Nodules: Prospective Safety and Efficacy Study - GÜLLÜOĞLU, MAHMUT BAHADIR; UĞURLU, MUSTAFA ÜMİT; YEGEN, ŞEVKET CUMHUR; UPRAK, TEVFİK KIVILCIM (SPRINGER, 2015)
Radiofrequency ablation (RFA) is a relatively novel procedure in the management of benign nodular goiter. This study was conducted to evaluate the safety and efficacy of ultrasound (US)-guided percutaneous RFA for benign symptomatic thyroid nodules as an alternative to surgery. The study involved patients for whom a fine needle aspiration biopsy had proved a diagnosis of benign nodular goiter and had nodule-related symptoms such as dysphagia, cosmetic problems, sensation of foreign body in the neck, hyperthyroidism due to autonomous nodules or fear of malignancy. Percutaneous RFA was performed as an outpatient procedure under local anesthesia. The primary outcome was an evaluation of the changes in symptom scores (0-10) for pain, dysphagia and foreign body sensation at the 1st, 3rd, and 6th months after the RFA procedure. Secondary outcomes were assessing volume changes in nodules, complication rates, and changes in thyroid function status. A total of 33 patients (24 % female, 76 % male) and a total of 65 nodules were included into the study. More than one nodule was treated in 63.6 % of the patients. We found a statistically significant improvement from baseline to values at the 1st, 3rd, and 6th months, respectively, as follows: pain scores (2.9 +/- A 2.7, 2.3 +/- A 2.01, 1.8 +/- A 1.7, and 1.5 +/- A 1.2, p 0.005), dysphagia scores (3.9 +/- A 2.7, 2.6 +/- A 1.9; 1.7 +/- A 1.6, and 1.1 +/- A 0.3, p 0.032), and foreign body sensation scores 3.6 +/- A 3, 2.5 +/- A 2.2; 1.6 +/- A 1.5, and 1.1 +/- A 0.4, p 0.002).The mean pre-treatment nodule volume was 7.3 +/- A 8.3 mL. There was a statistically significant size reduction in the nodules at the 1st, 3rd, and 6th months after RFA (3.5 +/- A 3.8, 2.7 +/- A 3.4, and 1.2 +/- A 1.7 mL, p 0.002). The volume reduction was found to be 74 % at 6th months following the RFA (p 0.005). 8 patients had autonomously functioning nodules in the pre-treatment period, 50 % (n: 4) became euthyroid at the 6th month after RFA. There were no complaints other than pain (12 %). RFA can be an alternative treatment modality in the management of benign symptomatic thyroid nodules. The results showed that it is a safe and effective procedure.
Keywords: PERCUTANEOUS ETHANOL INJECTION; THERMAL ABLATION; FOLLOW-UP; MANAGEMENT; GOITER; LEVOTHYROXINE; CARCINOMA; THERAPY; DISEASE; HEMITHYROIDECTOMY